2022
DOI: 10.1159/000523852
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Administration of Nintedanib Ameliorates Fibrosis Progression in CG-Induced Peritoneal Fibrosis Mouse Model

Abstract: <b><i>Background:</i></b> A multiple-target tyrosine kinase inhibitor, nintedanib, which is approved for treatment of interstitial pulmonary disease, has been demonstrated to have anti-fibrotic activity outside of the lungs. We explored its therapeutic effect in a murine model of peritoneal fibrosis. <b><i>Methods:</i></b> Daily intraperitoneal injections of chlorhexidine gluconate (CG) induced peritoneal fibrosis in mice. The effects of delayed administration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…A study by Yang et al (2021) showed that activation of STAT3/HIF1A signaling mediated mesothelial to mesenchymal transition and ultimately alleviated peritoneal fibrosis. MMP2 expression increased after Chlorhexidine Gluconate-induced peritoneal fibrosis, which may be related to ECM degradation ( Cui et al, 2022 ). BAX, PIM1, AR, and others are involved in signaling pathways such as apoptosis, cell migration, and metabolism which also involved in peritoneal fibrosis ( Li et al, 2022b ).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Yang et al (2021) showed that activation of STAT3/HIF1A signaling mediated mesothelial to mesenchymal transition and ultimately alleviated peritoneal fibrosis. MMP2 expression increased after Chlorhexidine Gluconate-induced peritoneal fibrosis, which may be related to ECM degradation ( Cui et al, 2022 ). BAX, PIM1, AR, and others are involved in signaling pathways such as apoptosis, cell migration, and metabolism which also involved in peritoneal fibrosis ( Li et al, 2022b ).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, inhibition of the STAT3 signaling pathway is associated with increased expression of E-cadherin ( 58 60 ), decreased expression of MMP-9 ( 61 – 63 ) and suppressed induction of EMT ( 58 ). Therefore, AGEs in MSpf may suppress EMT by decreased STAT3 signaling through the reduction of RAGE.…”
Section: Discussionmentioning
confidence: 99%